Técnicas de redacción de documentos y su incidencia en el entorno laboral de las secretarias de la Facultad de Ciencias Jurídicas Sociales de la Educación de la Universidad Técnica de Babahoyo - Lombeida Veloz, Martha Lisbett (2022)
The purpose of the current research was to know the document drafting techniques and their impact on the work environment of the secretaries of the Faculty of Legal Sciences of Education of the Technical University of Babahoyo. For this reason, a mixed qualitative and quantitative research was carried out with the analytical and descriptive methodology with statistical methods where a survey was carried out through Google Forms of a total of 14 secretaries of the faculty of legal sciences of education of the technical university of Babahoyo. A self-assessment questionnaire is run using the Likert scale where its survey results were that the institution should pay much more attention and conduct seminars on writing documentation where that would help the secretaries to have much more knowledge where they currently have a good level in drafting, but they want better preparation.